Strategic Reserves versus Market-wide Capacity Mechanisms - Pär Holmberg; Thomas P. Tangerås (Research Institute of Industrial Economics (IFN), 2021)
Many electricity markets use capacity mechanisms to support generation owners. Capacity payments can mitigate imperfections associated with "missing money" in the spot market and solve transitory capacity shortages caused by investment cycles, regulatory changes, or technology shifts. We discuss capacity mechanisms used in different electricity markets around the world. We argue that strategic reserves, if correctly designed, are likely to be more efficient than market-wide capacity mechanisms. This is especially so in electricity markets that rely on substantial amounts of intermittent generation, hydro power, and energy storage whose available capacity varies with circumstances and is difficult to estimate.
Keywords: D25; D47; Q40; Q48; 330; Capacity mechanism; Market design; Reliability; Resource efficiency